Building Independence: Empowerment Strategies for Small and Medium Enterprises of Matting Artisans in Babakan Village, Ciseeng District, Bogor Regency - Johan Wahyudhi; Halid Halid; Amelia Zakiyatun Nufus; Eva Latifah Hanum (Majapahit Journal of Islamic Finance and Management, 2025)
This article explores microeconomic empowerment efforts as a strategy to combat poverty in Babakan Village, Ciseeng Subdistrict, Bogor Regency, through a microbusiness capital loan scheme. The background to this activity is based on the limited access to capital for low-income communities, which hinders the development of small businesses and the improvement of family welfare. The method used is a participatory approach based on community empowerment with stages of needs identification through observation and interviews, joint program planning with village officials and business groups, distribution of revolving capital loans without collateral with intensive assistance, and periodic monitoring and evaluation of business development. The results of the activity showed that the micro-business capital loan program, accompanied by mentoring, was able to increase the turnover and stability of participants' businesses, strengthen financial literacy, and foster household economic independence. In addition, social solidarity among group members was created through a mechanism of shared responsibility for loan repayment. Thus, the empowerment strategy based on access to capital and continuous mentoring proved to be an effective model for poverty alleviation at the village level.